Applications and Reliability of Dorsal Metacarpal Artery Perforator Flap - Anand Prasath Jayachandiran; Suresh Rajendran; Surya Rao Venkata Mahipathy; Alagar Raja Durairaj; Narayanamurthy Sundaramurthy; Manoj Ananthappan (Indian Journal of Plastic Surgery)
Dorsal metacarpal artery perforator flap (DMAP), first described by Quaba and Davison, is a useful tool in the armamentarium of plastic surgeons. It provides like for like tissue for the reconstruction of dorsal finger defects. It is a simple and relatively easy flap to harvest with minimal donor site morbidity. In this case series, we present our experience, applications, and surgical technique of flap harvesting.